2018
DOI: 10.3892/mmr.2018.8711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes and biological pathways in bladder cancer

Abstract: The purpose of the present study was to identify key genes and investigate the related molecular mechanisms of bladder cancer (BC) progression. From the Gene Expression Omnibus database, the gene expression dataset GSE7476 was downloaded, which contained 43 BC samples and 12 normal bladder tissues. GSE7476 was analyzed to screen the differentially expressed genes (DEGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed for the DEGs using the DAVID database, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
(59 reference statements)
1
8
0
2
Order By: Relevance
“…Annotation of upregulated genes to cell cycle pathway and cell cycle related GO-BP terms might indicate the increased mitosis and cell division in bladder urothelial carcinoma cells. The upregulation of genes in cell division terms is consistent with previous report showing enrichment of differentially expressed upregulated genes in cell division and cell cycle related terms in bladder cancer [5]. According to KEGG pathway and GO-BP term annotations, downregulated genes in bladder urothelial carcinoma cells mostly annotated to adhesion, ECM-receptor interaction, cardiomyopathy related pathways, muscle related and circulatory system related GO-BP terms (Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Annotation of upregulated genes to cell cycle pathway and cell cycle related GO-BP terms might indicate the increased mitosis and cell division in bladder urothelial carcinoma cells. The upregulation of genes in cell division terms is consistent with previous report showing enrichment of differentially expressed upregulated genes in cell division and cell cycle related terms in bladder cancer [5]. According to KEGG pathway and GO-BP term annotations, downregulated genes in bladder urothelial carcinoma cells mostly annotated to adhesion, ECM-receptor interaction, cardiomyopathy related pathways, muscle related and circulatory system related GO-BP terms (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The increased expression of genes in bladder cancer found to be annotated to negative regulation apoptotic process, salmonella infection, amoebiasis, malaria pathways and rheumatoid arthritis pathways, while downregulated genes were annotated to oxidative phosphorylation, taurine and hypotaurine metabolism, vitamin digestion and absorption, arthritis and vibrio cholerae infection pathways [7]. Enrichment of upregulated genes in cell division and protein binding, enrichment of downregulated genes in extracellular matrix organization and complement and coagulation cascades was also reported [5]. Studies with TCGA datasets of bladder cancer mainly focus on genomic analysis of DNA alterations, including variations and mutations, and related pathways [8][9][10][11].…”
Section: Functional Annotation Of Differentially Expressed Genesmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, hormone inhibitors, such as angiotensin system inhibitors were applied to improve the prognosis of PDAC (27). KEGG pathway analysis demonstrated that the upregulated genes were predominantly involved in 'ECM-receptor interaction' and the 'cGMP-PKG signaling pathway', which has been identified as a key signaling pathway in different types of cancer, including bladder cancer (28). A total of 18 hub genes were discovered following construction of the PPI network, in which three key genes (ASPM, BUB1B and SPDL1) were demonstrated to be enriched in the cell cycle biological processes/pathways, and were significantly associated with both shorter OS and DFS in patients with PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the raw data by GEO2R (www.ncbi.nlm.nih.gov/geo/geo2r/). Statistically significant DEGs were defined with P value <0.01 and a |log2 fold change (FC)| ≥1 as the thresholds described in the references [32][33][34] .…”
Section: Data Preprocessing and Identification Of Degsmentioning
confidence: 99%